2012
DOI: 10.1016/j.polymer.2012.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological properties of electrospun PA 6(3)T fiber mats

Abstract: (G. C. Rutledge). AbstractThe mechanical and tribological properties of electrospun fiber mats are of paramount importance to their utility as components in a large number of applications. Although some mechanical properties of these mats have been reported previously, reports of their tribological properties are essentially nonexistent. In this work, electrospun nanofiber mats of poly(trimethyl hexamethylene terephthalamide) (PA 6(3)T) with average fiber diameter of 463±64 nm are characterized mechanically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…A vertically aligned, parallel plate setup was used for electrospinning, as described elsewhere [24]. …”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…A vertically aligned, parallel plate setup was used for electrospinning, as described elsewhere [24]. …”
Section: Fabricationmentioning
confidence: 99%
“…The as-spun mats were annealed thermally in a furnace (Thermolyne Industrial Benchtop Furnace, FD1545M) to strengthen the electrospun mat, as previously reported [24]. The mats were held in plane during the annealing process by draping over a petri dish that is 10 cm in diameter.…”
Section: Post-processingmentioning
confidence: 99%
“…To form thee-layered composite membranes, a nonwoven electrospun PS or PS:PSU mat was sandwiched between two electrospun nonwoven CA mats and hotpressing at 80 °C under 4,000 lbs load for 5 min, as described elsewhere (Mannarino and Rutledge, 2012). Disks (3.7 cm in diameter) were cut from the three-layered membranes and sandwiched between two pieces of aluminum tape (Han and Martin, 2009) having circular openings to expose an effective membrane area of 0.95 cm 2 .…”
Section: Three-layered Membrane Preparationmentioning
confidence: 99%
“…Parallel-plate electrospinning apparatus ( Figure 1a) was used to create flexible nonwoven mats of polysulfone fibers (average fiber diameter of 1.69 ± 0.17 µm and mat thickness = 103 ± 2 µm, Figure 1b) from organic polymer solutions using a protocol Submitted to 6 6 modified from a previous report. [13] Polysulfone was chosen as a polymer substrate because it has high chemical resistance and good thermal and mechanical stability. [14] The nonwoven mats have an inherently high porosity of 85.1 ± 1.1%, which was determined by a gravimetric method described elsewhere.…”
Section: Submitted To 4mentioning
confidence: 99%
“…[14] The nonwoven mats have an inherently high porosity of 85.1 ± 1.1%, which was determined by a gravimetric method described elsewhere. [13] Once the ES fiber mat was generated, it was first treated with one minute of air plasma to improve the wettability by introducing hydroxyl and charged carboxylated groups on the surface. [15] The ES fiber mat was then immediately immersed into a 0.2 wt.% aqueous solution of branched polyethylenimine (BPEI) for 10 min to impart positive charge on the surface of ES fibers.…”
Section: Submitted To 4mentioning
confidence: 99%